Kant's theory of a priori knowledge - Greenberg, Robert, 1934-2024 (University Park, PA : Pennsylvania State University Press, 2001)
The prevailing interpretation of Kant's First Critique in Anglo-American philosophy views his theory of a priori knowledge as basically a theory about the possibility of empirical knowledge (or experience), or the a priori conditions for that possibility (the representations of space and time and the categories). Instead, Robert Greenberg argues that Kant is more fundamentally concerned with the possibility of a priori knowledge--the very possibility of the possibility of empirical knowledge in the first place.Greenberg advances four central theses:(1) the Critique is primarily concerned about the possibility, or relation to objects, of a priori, not empirical knowledge, and Kant's theory of that possibility is defensible; (2) Kant's transcendental ontology must be distinct from the conditions of the possibility of a priori knowledge; (3) the functions of judgment, in Kant's discussion of the Table of Judgments, should be seen according to his transcendental logic as having content, not as being just logical forms of judgment making; (4) Kant's distinction between and connection of ordering relations (Verhaltnisse) and reference relations (Beziehungen) have to be kept in mind to avoid misunderstanding the Critique. At every step of the way Greenberg contrasts his view with the major interpretations of Kant by commentators like Henry Allison, Jonathan Bennett, Paul Guyer, and Peter Strawson. Not only does this new approach to Kant present a strong challenge to these dominant interpretations, but by being more true to Kant's own intent it holds promise for making better sense out of what have been seen as the First Critique's discordant themes.
Frontmatter -- CONTENTS -- Preface -- PART ONE: INTRODUCTION -- 1 The Problem: The Possibility of A Priori Knowledge -- 2 Kant's External Realism -- 3 A Synopsis of the Solution to the Problem of A Priori Knowledge -- 4 A Model of Kant's Theory of Representation -- PART TWO: TRANSCENDENTAL ONTOLOGY -- 5 Interpretation of Text; Theory and View -- 6 Monism or Dualism? -- 7 The Necessity of Kant's Idealism -- 8 Sensibility and the Understanding, Appearances and Things in Themselves -- PART THREE: TRANSCENDENTAL LOGIC -- 9 The Content of Kant's Logical Functions of Judgment -- 10 Kant's Categories Reconsidered -- 11 Three Issues in Step One of the B-Deduction -- 12 Judgment, Consciousness, and the Categories -- 13 Perception and the Categories -- 14 The Transcendental Character of the Second Analogy -- PART FOUR: REVIEW -- 15 Transcendental Epistemology -- Index
JSTOR
Keywords: Kant, Immanuel, -- 1724-1804.; A priori -- History -- 18th century; A priori -- Histoire -- 18e siècle.; PHILOSOPHY / Criticism